2019
DOI: 10.29244/jmo.v9i3.28224
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Produk pada McDonald’s di Jatiasih Bekasi

Abstract: The development of new era leads people to be fast and practical person on all activity. Include culture of choosing food and drink consumers choose  fast food. The purpose of this study was to identify the characteristics of consumers, analyze the purchasing decision making process, and analyze the factors that influence consumer decision making. The method used in this research is a descriptive analysis and factor analysis use SPSS 25 for windows. The research result consumers characteristic at McDonald’s Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
0
1
1
9
Order By: Relevance
“…Adequate policies to help secure the food prices are undoubtedly required to maintain proper stable food consumption and purchase in rural areas. This finding was contrary to a study by (Basith & Fadhilah, 2019) that showed that living location did not implicate consumer purchasing decisions.…”
Section: Factors That Influenced the Household Consumption Decision O...contrasting
confidence: 99%
“…Adequate policies to help secure the food prices are undoubtedly required to maintain proper stable food consumption and purchase in rural areas. This finding was contrary to a study by (Basith & Fadhilah, 2019) that showed that living location did not implicate consumer purchasing decisions.…”
Section: Factors That Influenced the Household Consumption Decision O...contrasting
confidence: 99%
“…Penelitian serupa dilakukan oleh Nasution & Putri (2018) memiliki hasil yang berbeda, faktor yang dapat memberikan pengaruh terhadap keputusan pembelian online, yaitu kemudahan, gaya hidup, dan harga. Serta penelitian Basith & Fadhilah (2018) menunjukkan faktor yang mempengaruhi keputusan pembelian produk oleh konsumen McDonald's, yaitu faktor pengaruh lingkungan, kebiasaan individu, bauran promosi produk, aktifitas, waktu, daya tarik produk, asumsi pribadi, keunikan produk, pengetahuan, dan kondisi fisik.…”
Section: Pendahuluanunclassified
“…Sebanyak 70 persen responden berjenis kelamin perempuan, hal ini sejalan dengan penelitian yang dilakukan oleh Fitriani (2019) yang menjelaskan bahwa kaum perempuan memiliki kecenderungan lebih mudah mengambil keputusan pembelian untuk produk dan dikuatkan Basith and Fadhilah (2019) meskipun berbeda dengan hasil penelitian dari Sosianika dan Juliani (2017) bahwa tidak terdapat perbedaan perilaku pembelian impulsif berdasarkan jenis kelamin. Jenis kelamin lakilaki yang memberikan respon sebesar 30% dari total responden.…”
Section: Penyajian Data Analisis Strata Produk Dan Analisis Pesaing P...unclassified